The man who listens to horses - Lcaldwell, Taylpor 1935- (New York : Ballantine Books)
This is the story of a young man that learns to communate with horses.
Keywords: Horses -- Behavior; Horses -- Training; English fiction; Horse trainers -- California -- Biography; Horse whisperers -- California -- Biography